2019
DOI: 10.3748/wjg.v25.i41.6258
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameters score predicts long-term outcomes in stage II-III gastric cancer patients

Abstract: BACKGROUNDIncreasing numbers of laboratory blood parameters (BPM) have been reported to greatly affect the long-term outcomes of gastric cancer (GC) patients. However, the existing prognostic models do not comprehensively analyze these predictors.AIMTo construct a new prognostic tool, based on all the prognostic BPM, to achieve more accurate prognosis prediction for GC.METHODSWe retrospectively assessed 850 consecutive patients who underwent curative resection for stage II-III GC from January 2010 to April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This may result in a considerable loss of statistical power with introduction of bias in the multiple regression analysis (13). However, considering those inflammatory biomarkers as categorical variables may be more appropriate in guiding process of clinical decision-making as continuous variables could not necessarily increase the prediction performance (14). Therefore, the serum inflammatory biomarkers in our study were divided as binary variables and valued as 0 or 1 based on their optimal cut-off value instead of absolute value.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a considerable loss of statistical power with introduction of bias in the multiple regression analysis (13). However, considering those inflammatory biomarkers as categorical variables may be more appropriate in guiding process of clinical decision-making as continuous variables could not necessarily increase the prediction performance (14). Therefore, the serum inflammatory biomarkers in our study were divided as binary variables and valued as 0 or 1 based on their optimal cut-off value instead of absolute value.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hematological biomarkers, such as the level of lymphocytes, neutrophils, platelets, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C-reactive protein, are now commonly measured and applied in the assessment of systemic in ammatory response [8,9] . In fact, previous studies have con rmed that parameters are potential prognostic markers in patients with solid tumors [10][11][12][13] . Conversely, other research works have reported contradictory results on the prognostic values [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative total bilirubin (TB) is a critical biomarker for the diagnosis of biliary obstruction and is present at the first diagnosis for the majority of AC patients. In addition, preoperative albumin has been widely used for defining immune and nutritional statuses[ 4 ]. Recently, several studies have proven that the preoperative fibrinogen-albumin ratio (FAR) is a significant prognostic biomarker in multiple tumor types, including lung cancer[ 5 ], hepatocellular carcinoma[ 6 ], colorectal cancer[ 7 ], gastric cancer[ 8 ], bladder cancer[ 9 ], and rectal cancer[ 10 ].…”
Section: Introductionmentioning
confidence: 99%